Autoimmune Hepatitis: Clinical Overview and Pathological Findings - Gill, MD, Simpal (North American Journal of Medicine and Science, 2018)
Autoimmune hepatitis (AIH) is an uncommon cause of severe chronic hepatitis with a female predilection and affecting all ages and ethnic groups. Although its pathogenesis is still not completely clear, the condition has been linked to dysimmunoregulation of T lymphocytes, which attack and damage the hepatic parenchyma. Characteristic autoantibodies are produced against hepatocytes leading to cell injury and necrosis, eventually progressing to cirrhosis in a subset of patients. The goal of treatment is to prevent or halt disease progression by immunosuppressive therapy. Liver transplantation is the choice of treatment in selected patients with end stage liver disease, acute liver failure or hepatocellular carcinoma. Up to a third of post-transplanted patients have AIH recurrence in the allograft. The overall prognosis is good with high mortality in untreated cases. [N A J Med Sci. 2018;11(1):6-10. DOI: 10.7156/najms.2018.110106]